ANALISIS PEMANFAATAN LIMBAH TAHU DALAM MENINGKATKAN PENDAPATAN PENGRAJIN PADA UMKM TAHU (Studi Kasus Pada Pengrajin Tahu di Kecamatan Sungai Bahar Kabupaten Muaro Jambi) - Pratiwi Indah Sari, Sentaulina Simanungkalit, (SJEE (Scientific Journals of Economic Education), 2019)
Abstract This study aims to determine (1) To determine the management of the utilization of Tofu waste produced by Tofu craftsmen in Sungai Bahar District, Muaro Jambi Regency. (2) To find out the income of Tofu UMKM in Sungai Bahar District before and after the utilization of Tofu waste. The results showed that (1) Management of the utilization of tofu waste produced by craftsmen at Tofu MSMEs in Sungai Bahar District in the form of products that have a sale value, Tofu MSMEs in Sungai Bahar District utilize liquid and solid waste which from five MSMEs Tofu in the Sungai Bahar Subdistrict there are 2 Tofu MSMEs that utilize liquid waste that is processed to produce liquid fertilizer products, and there are 2 Tofu MSMEs that utilize solid waste which is processed as a consumable product, that is gembus. The products produced from the use of waste have a sale value that can increase the income of craftsmen in Tofu MSMEs who use Tofu waste, and there are 1 Tofu MSMEs that make Tofu waste as a form of social Human. (2) Income in Sungai Bahar Subdistrict prior to the utilization of Tofu waste is income from the sale of Tofu products, income received by Tofu UMKM after utilization of Tofu waste is income before being combined with income received from the sale of liquid fertilizer and fertilizer. Keywords : Tofu Waste Management, Tofu MSME Revenue